Dynamics of weeds and their management through herbicides in zero tilled wheat (Triticum aestivum) - DHYANI, VIPIN CHANDRA; MISRA, R D (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted in silty clay loam soil of Pantnagar during rabi season of 2003-04 and 2004-05 to study weed dynamics and to work out optimum dose and timing of different herbicides in zero tilled wheat. Total weed population in weedy plots was highest at 60 days stage. P. minor dominated the field at 30 days stage and at harvest while population of C. didymus was highest at 60 and 90 days stage. Perennial weeds were higher in zero tillage than conventional tillage. All the herbicides reduced density and dry weight of weeds, however, sulfosulfuron at 25 g/ha after first irrigation was most effective in controlling weeds and obtaining highest wheat grain yield and net return also. All the herbicides were more effective when they were applied at higher dose and after first irrigation. Highest grain yield were obtained in conventionally tilled wheat, however, net returns (Rs/ha) were higher in zero tilled wheat.